Structures of tmRNA and SmpB as they transit through the ribosome - Charlotte Guyomar; Gaetano D’Urso; Sophie Chat; Emmanuel Giudice; Reynald Gillet (Nature Communications, 2021)
Trans-translation, mediated by small protein B (SmpB) and transfer-messenger RNA (tmRNA), enables recycling of the ribosomes stalled on defective mRNAs in bacteria. Here, the authors report structures of the ribosome during trans-translation that reveal a translocation intermediate and elucidate the movements of the tmRNA-SmpB complex in the ribosome.